O consumo de álcool segundo as gravuras Beer Street e Gin Lane de William Hogarth e as obras de John Wesley: convergências e diferenças Alcohol consumption as portrayed in William Hogarth's prints Beer Street and Gin Lane and in the works of John Wesley: similarities and differences - Helmut Renders (História, Ciências, Saúde: Manguinhos, 2012)
Compara as gravuras Gin Lane e Beer Street, de William Hogarth, com textos do seu contemporâneo John Wesley, spiritus rector do movimento religioso metodista. Embora em algumas gravuras Hogarth tenha retratado o movimento metodista como perigosamente entusiasta, os dois defenderam uma agenda próxima quanto ao consumo de álcool. A semelhança entre as duas formas de compreender a questão é explicada por costumes culturalmente estabelecidos, e a diferença por uma perspectiva social distinta. The article compares William Hogarth's Gin Lane and Beer Street with texts by his contemporary John Wesley, spiritus rector of the Methodist movement. Although Hogarth had portrayed the Methodist religious movement in some of his prints as dangerously enthusiastic, both men defended a similar agenda concerning alcohol consumption. The similarities in their two ways of understanding the issue can be explained by culturally established customs, while distinct social outlooks can account for their differences.